The relationship between alexithymia, shame, trauma, and body image disorders: investigation over a large clinical sample - Franzoni, Emilio (Dove Medical Press, 2013)
BACKGROUND: The connections between eating disorders (EDs) and alexithymia have not been fully clarified. This study aims to define alexithymia’s connections with shame, trauma, dissociation, and body image disorders. METHODS: We administered the Dissociative Experience Scale-II, Trauma Symptom Inventory, Experience of Shame Scale, Toronto Alexithymia Scale-20, and Body Uneasiness Test questionnaires to 143 ED subjects. Extensive statistical analyses were performed. RESULTS: The subjects showed higher scores on alexithymia, shame, dissociation, and traumatic feelings scales than the nonclinical population. These aspects are linked with each other in a statistically significant way. Partial correlations highlighted that feelings of shame are correlated to body dissatisfaction, irrespective of trauma or depressed mood. Multiple regression analysis demonstrates that shame (anorexic patients) and perceived traumatic conditions (bulimic and ED not otherwise specified) are associated with adverse image disorders. CONCLUSION: Shame seems to hold a central role in the perception of an adverse self-image. Alexithymia may be interpreted as being a consequence of previous unelaborated traumatic experiences and feelings of shame, and it could therefore be conceptualized as a maladaptive–reactive construct.